The Settlement of Mining Disputes and The Implementation of International Arbitration Awards - Suwarsit Suwarsit; Yoyo Arifardhani (Pandecta Research Law Journal, 2022)
Article 154 of the Law of the Republic of Indonesia Number 4 of 2009 concerning Mineral and Coal Mining has regulated dispute resolution through domestic courts and arbitration. In fact, the dispute resolution such as the divestment cases of PT Newmont Nusa Tenggara and PT Kaltim Prima Coal was settled at the International Arbitration Institute. Furthermore, the resolution of the dispute over the divestment of mineral and coal mining shares against PT Newmont Nusa Tenggara and PT Kaltim Prima Coal through the International Arbitration Institute was accepted and some were rejected. The purpose of this research is to find the settlement of mineral and coal mining disputes and the implementation of international arbitration decisions. The results of the study show that in addition to resolving mineral and coal mining disputes, contracts made by mining business actors with the Government of Indonesia, both Contracts of Work and Coal Mining Concession Work Agreements, dispute resolution is carried out through International Arbitration institutions besides being regulated through courts and domestic arbitration. The implementation of international arbitral awards according to Indonesian law must meet several conditions, one of which is that the decision is handed down by an arbitrator or arbitral tribunal in a country with the Indonesian state bound by agreements, both bilaterally and multilaterally. Regarding the recognition and implementation of international arbitration awards, if the starting point is Article 3 in the New York Convention, a request for recognition and execution from one of the participating countries to a participant in another country must be executed, but Article 5 of the New York Convention provides the possibility for a participating country to refuse it.